Pre-treatment of Used-Cooking Oil as Feed Stocks of Biodiesel Production by Using Activated Carbon and Clay Minerals - Syah Putra, Rudy; Shabur Juliantoa, Tatang; Hartono, Puji; Dyah Puspitasaria, Ratih; Kurniawan, Angga (International Journal of Renewable Energy Development, 2014)
Many low-cost feedstock i.e. used-cooking oil (UCO) for the production of biodiesel fuel (BDF) has contained a large amount of water and high proportion of free fatty acids (FFAs). Therefore, a pre-treatment process to reduce the water content (<0.1 wt.%) and FFAs (<2.0 wt.%) were necessary in order to avoid an undesirable side reactions, such as saponification, which could lead to serious problem of product separation and low fatty acid methyl ester (FAME) yield. . In this study, a pre-treatment process of used cooking oil as a feedstock for the production of BDF by using various adsorbents such as Activated Carbon (AC) and various clay minerals, for example Smectite (S), Bentonite (B), Kaolinite (K), and Powdered Earthenware (PE) were evaluated. The oil obtained from pre-treatment was compared with oil without pre-treatment process. In this study, we reported a basic difference in material ability to the oil, depending on the adsorption condition with respect to the physico-chemical parameters, e.g. refractive index (R), density (Ï), FFAs, and water content (W). The results showed that the water content and FFAs in the oil has decreased when using AC as an adsorbent compared with clay minerals. However, the refractive index of oil has similar with the oil without pre-treatment process as well; meanwhile, the density of oil has increased after the pre-treatment process by using clay minerals.